Digitalization Training for MSMEs to Increase Competitiveness in the Digital Era - Sitohang, Ance Marintan D; Fachrudin, Khaira Amalia; Sibarani, Magdalena Linda Leonita; Ivan Jaya (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
MSMEs in Indonesia are the most important and strong pillars of economic development. Its role in driving the rate of economic growth and employment is huge. MSME MUA RiasaNeni is an MSME that operates in cosmetology services. The problems that occur with UMKM MUA RiasaNeni are the limited human resources of UMKM MUA RiasaNeni in creating interesting content on social media as promotional media, the limited supporting tools they have especially for the need to develop content, and the absence of financial bookkeeping that is used to record all financial transactions, for keeping records of all financial transactions precisely and systematically. The solution taken by the service team was to provide training to UMKM MUA RiasaNeni actors. Activities were carried out at PTPN IV Emplasmend Kebun Laras, Bandar Huluan District, Simalungun Regency.